2009
DOI: 10.2527/jas.2009-2003
|View full text |Cite
|
Sign up to set email alerts
|

Absorption and metabolism of benzoic acid in growing pigs1

Abstract: Dietary benzoic acid (BA) supplementation causes a pronounced reduction in urinary pH but only small changes in blood pH. The present study aimed to investigate the portal absorption profile, hepatic metabolism of BA, and renal excretion of hippuric acid (HA) underlying the relatively small impact of BA on systemic acid-base status. Eight growing pigs (BW = 63 +/- 1 kg at sampling) fitted with permanent indwelling catheters in the abdominal aorta, hepatic portal vein, hepatic vein, and mesenteric vein were all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
46
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(47 citation statements)
references
References 14 publications
1
46
0
Order By: Relevance
“…In a study of Kristensen et al (2009), adding 1% benzoic acid to a diet for growing pigs markedly acidified the urine pH (about 2 points), but only slightly reduced blood pH and no effects of benzoic acid supplementation were detected on inter-organ fluxes of O2, CO2, glucose, lactate and urea. Similarly, Kluge et al (2010) found a decrease in urine pH with the addition of 0.5% benzoic acid to the diet of sows.…”
Section: Introductionmentioning
confidence: 99%
“…In a study of Kristensen et al (2009), adding 1% benzoic acid to a diet for growing pigs markedly acidified the urine pH (about 2 points), but only slightly reduced blood pH and no effects of benzoic acid supplementation were detected on inter-organ fluxes of O2, CO2, glucose, lactate and urea. Similarly, Kluge et al (2010) found a decrease in urine pH with the addition of 0.5% benzoic acid to the diet of sows.…”
Section: Introductionmentioning
confidence: 99%
“…The blood samples taken in Experiment 2 on day 18 were obtained 3 h after feeding to assure a steady Val absorption. This time point was set up based on our own data obtained in Experiment 1 and on measurements on absorption kinetics in pigs showing a maximum absorption of nutrients from 0.5 to 2 h after feeding whereafter it decreases until~6 h post-feeding (Rerat et al, 1993;van der Meulen et al, 1997;Kristensen et al, 2009). Although the AA in focus was Val, other AA and metabolites were also measured.…”
Section: Discussionmentioning
confidence: 99%
“…The present experiment demonstrated that dietary interventions can decrease slurry pH to an extent that emissions of NH 3 are significantly reduced. The observed decrease in slurry pH may be explained by a decrease in the pH of urine (Kristensen et al, 2009;Nørgaard et al, 2010aNørgaard et al, , 2010b. The pH drop resulted in significant reductions in NH 3 emissions of 28 to 40%, least for +BA and most for the two treatments with CaCl 2 .…”
Section: Ammonia Emissionsmentioning
confidence: 99%
“…Benzoic acid (BA) is approved in the European Union as an ingredient in diets for fattening pigs at a level between 5 and 10 g kg -1 (European Commission, 2007), and BA is effective in decreasing urinary pH by voiding hippuric acid, which is produced in the liver from metabolism of BA (Kristensen et al, 2009;Nørgaard et al, 2010aNørgaard et al, , 2010b. The use of acids in diets for pigs elicits an antimicrobial effect and increases gain (Kluge et al, 2006).…”
mentioning
confidence: 99%